2016
DOI: 10.11648/j.ijefm.20160403.14
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Inventory Control Practices on Procurement Performance of Agrochemicals Distributors in Nakuru Central Sub-County, Kenya

Abstract: Abstract:The purpose of this study was to establish the Influence of inventory control practices and procurement performance of Agrochemical Distributors in Nakuru Central Sub-County. The study was a survey as it sought to determine the relationship between internal inventory control and procurement performance in agrichemical distributors in Nakuru Central sub-county within limited time frame. The respondents in this study were the employees in Agrochemical Distributors in Nakuru Central Sub-County. Data was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…(Folinas & Shen, 2014) found no link between inventory turnover and financial performance. (Onchoke & Wanyoike, 2016) found a significant positive influence of internal inventory security procedural practices, inventory auditing and computerized inventory control, on procurement performance. In (Lwiki et al, 2013), the study result revealed that there a positive correlation between inventory management and return on sales exists.…”
Section: Literature Reviewmentioning
confidence: 95%
“…(Folinas & Shen, 2014) found no link between inventory turnover and financial performance. (Onchoke & Wanyoike, 2016) found a significant positive influence of internal inventory security procedural practices, inventory auditing and computerized inventory control, on procurement performance. In (Lwiki et al, 2013), the study result revealed that there a positive correlation between inventory management and return on sales exists.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Comparatively speaking, traditional cost systems, which usually depend on a small number of volume-based metrics, like direct labor hours or sales volume, assign costs less accurately than when numerous drivers are used (Krumwiede and Roth, 1997). Customers, suppliers, goods, and supply chains that are a part of these operations are allotted charges by ABC [15,16]. EOQ is a model that is frequently utilized to manage inventory in a variety of industries, according to writers like Blackburn (2010).…”
Section: Influence Of Jit Model On Operationalmentioning
confidence: 99%
“…Okundi (2011) also observed that SACCOs suffer challenges of their members preferring loans from commercial banks because the amount of loans rewarded to them by commercial banks is not pegged on savings as in the case of SACCOs. Since there was an empirical evidence that interest rate have a significant effect on financial performance (Ndegwa, Waweru and Huka, 2016;Kariuki and Ngahu, 2016;Ngumi, 2014;Khan and Sattar, 2014;Onyekachi and Okoye, 2013), a critical analysis of effect of interest rate on financial performance of SACCOs in Kenya was inevitable. This would help in developing a favourable interest rate for better performance of SACCOs that had been rocked with a number of challenges.…”
Section: Problem Statementmentioning
confidence: 99%
“…This study analyzed the banking behavior in Africa and interest rate emanates from the study findings as one of the factors affecting lending behavior. Kariuki and Ngahu (2016) examined the effect of interest rates on loan performance of Microfinance Institutions in Naivasha Sub-County, Kenya. The study used survey research design and found out that there was a strong relationship between interest rate and loan performance (loan repayment).…”
Section: Empirical Reviewmentioning
confidence: 99%
See 1 more Smart Citation